Effect of social media-based education on self-care status, health literacy, and glycated hemoglobin in patients with type 2 diabetes - Ali Safdari; Nazi Nejat; Abdollah Abolfathi; Fatemeh Mehrabi; Fatemeh Rafiei (Frontiers in Public Health)
ObjectivesThis study examines the impact of social media-based education on health literacy status, self-care, and glycosylated hemoglobin (HbA1c) in individuals with type 2 diabetes (T2D).MethodThis educational intervention study was carried out from March 2022 to June 2022 on diabetic patients visiting the diabetes clinic in Arak, Iran. The patients split into two groups: the virtual education group (n = 38) using the Telegram messaging platform and the control group (n = 38). Patients in the virtual education group received multimedia messages about T2D daily for 4 weeks. Data analysis utilized SPSS version 23 and statistical tests.ResultsThe results of this study showed that the overall score of health literacy and the dimensions of reading, understanding, and evaluation were significantly higher in the intervention group than in the control group (p < 0.05). However, the score for the access dimension did not show a significant difference between the two groups (p > 0.05). The Wilcoxon test results indicated that the average HbA1c score significantly decreased in the intervention group before and after the intervention. However, these changes were not significant in the control group. Nevertheless, the Mann–Whitney test did not indicate a significant statistical difference between the groups regarding the average HbA1c score before and after the intervention (p > 0.05).ConclusionThe findings of this study suggest that social networks provide a suitable platform for delivering self-care education to individuals with T2D. Furthermore, in the long term, it might positively impact the patients’ HbA1c levels. Future studies with larger sample sizes can be beneficial in this area.